2021
DOI: 10.3390/ijms22157940
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Prevents the WIN 55,212-2 Evoked Cross-Priming of Ethanol-Induced Conditioned Place Preference (CPP)

Abstract: The activation of the endocannabinoid system controls the release of many neurotransmitters involved in the brain reward pathways, including glutamate. Both endocannabinoid and glutamate systems are crucial for alcohol relapse. In the present study, we hypothesize that N-methyl-D-aspartate (NMDA) glutamate receptors regulate the ability of a priming dose of WIN 55,212-2 to cross-reinstate ethanol-induced conditioned place preference (CPP). To test this hypothesis, ethanol-induced (1.0 g/kg, 10% w/v, i.p.) CPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(86 reference statements)
1
1
0
Order By: Relevance
“…SUD memory is evaluated by the degree of preference of the animal for the condition context in the CPP model (Suzuki, 1999). That is, although direct exposure and drug induction occurred in the original conditioning chamber, the mice were able to retrieve the associative memory between the drug and the context (Marszalek‐Grabska et al., 2021; McKendrick & Graziane, 2020; Napier et al., 2013; Scherma et al., 2021), and our experiments are consistent with these results. However, studies on drug generalization in mice have not been reported, and studies have shown that fear generalization in mice depends on the similarity of cued information, such as shape (Yu et al., 2021; Zhou et al., 2017), sound (Pollack et al., 2018) and floor (Yu et al., 2021).…”
Section: Discussionsupporting
confidence: 87%
“…SUD memory is evaluated by the degree of preference of the animal for the condition context in the CPP model (Suzuki, 1999). That is, although direct exposure and drug induction occurred in the original conditioning chamber, the mice were able to retrieve the associative memory between the drug and the context (Marszalek‐Grabska et al., 2021; McKendrick & Graziane, 2020; Napier et al., 2013; Scherma et al., 2021), and our experiments are consistent with these results. However, studies on drug generalization in mice have not been reported, and studies have shown that fear generalization in mice depends on the similarity of cued information, such as shape (Yu et al., 2021; Zhou et al., 2017), sound (Pollack et al., 2018) and floor (Yu et al., 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the physiological and psychoactive effects of ethanol are because of several receptor systems activation. Including: N-Methyl-D-aspartate (NMDA), the action of ethanol consumption on activity of NMDA receptor are occurred by internalization and phosphorylation of receptor subunits which permit Ca2 + influx inside the cell, in turn promote long-term potentiation (LTP) induction, a key element of memory and learning, causing by example; to habit formation (24). Many studies have been shown that withdrawal effects of alcohol in brain regions is associated with elevation in transmission of excitatory amino acid and dopamine signaling alterations, resulting in executive functions deficits.…”
Section: Najim Et Al: Glutamate As a Target Therapy For Alcohol Depen...mentioning
confidence: 99%